From genealogy to blood:: the collective body in Sangria, by Luiza Romão - Lousa, Pilar Lago e (Opiniães, 2019)
Luiza Romão is a highly forceful contemporaneous poet that deconstructs, by means of her verses, entrenched hegemonic speeches, bringing to light gender, race and social class issues, through an intersectional feminist perspective. Inscribed in the marginal literature, the author is a pioneer in the slams movement and has opened doors for other writers to find their own voices in the oral poetry battles. Sangria (2017, Selo do Burro), her second book, retells the Brazilian history through a uterus perspective, as in a menstrual cycle. Twenty-eight poems problematize the place women occupy in society, the patriarchal structures, the misogynous and racist speech, turning the work into an assertive answer to the social and political situation into which the country has been immersed. Sangria is word about to be hurled, a cut that reveals cracks and violences. In this article, we aim to analyze the context in Luiza Romão is inserted, her poems, the book aesthetic conception, and the way literature is converted into a tool to rescue silenced voices and to fight back oppressive practices.